A Plasmonic Photonic Diode for Unidirectional Focusing, Imaging, and Wavelength Division De‐Multiplexing. Issue 4 (4th February 2014) - Zhang, Xinping; Zhang, Jian; Liu, Hongmei; Zhai, Tianrui
<x xml:space="preserve">Abstract</x> A thin‐film photonic lens is fabricated using chirped plasmonic grating structures, which enables off‐axis focusing and simultaneous de‐multiplexing of the incident light beams, as well as the intrinsic function of an optical lens for imaging. This planar two‐dimensional photonic device may be used either as a positive (converging) or a negative (diverging) lens through controlling how the light beam is incident and how the device is oriented, which defines multifold 'diode' effects and is thus termed "forward" or "backward" biasing of such a 'diode' lens. This plasmonic photonic diode (PPD) features by unidirectional functions instead of non‐reciprocal transmission. These unique functions are demonstrated by focusing different colors into different angles and different focal lengths with large dispersions, which enables direct wavelength division de‐multiplexing with high resolution and high efficiency. Strong plasmonic scattering by the gold nanolines that constitute the chirped grating structures leads to efficient operation and polarization‐dependent performance of the PPD device.